3D printing of plant fiber reinforced polymer composites (PFRC's): an insight into methods, challenges and opportunities. Issue 6 (13th April 2023) - Salunkhe, Sachin; Murali, Arun Prasad; Mohammed Abdel Moneam, Hussein; Naranje, Vishal; Shanmugam, Ragavanantham
ABSTRACT: Plant fibers over the years have succeeded in generating interest among researchers about their use. This is mainly due to several ecological legislations put in place by nations to counter the rise in global warming levels. Although plant fiber-based polymer composites are penetrating various domains, concern regarding their suitability and challenges related to manufacturing techniques needs to be addressed. This review attempts to discuss various aspects of plant fibers, their processing with polymer, and methods to improve the fib-matrix interaction. The article also presents an insight into different 3D printing techniques such as fused deposition modeling, laminated object manufacturing, stereolithography, selective laser sintering, and inkjet printer for processing fiber-based polymer composites. The use of technologically advanced 4D printing of fiber-polymer composites is also discussed. Challenges and futuristic opportunities associated with recent works on 3D printing techniques are analyzed toward the end. The paper is structured in the following manner: the first part focuses on natural fibers with their constituents, their processing, and manufacturing techniques with polymers, while the second part of the paper discusses various 3D printing techniques with their challenges and opportunities.